Production of biofuels by using chlorella vulgaris and chlamydomonas reinhardtii In different media - Puteri Ezzah Syafiah, Mohd Saifu (2025)
This study investigated the growth, lipid accumulation, and fatty acid profiles of two microalgae species, Chlorella vulgaris and Chlamydomonas reinhardtii, cultivated in three different media (BG-11, BBM, and CHU-10). The results revealed that Chlorella vulgaris thrived best in BBM medium while Chlamydomonas reinhardtii showed optimal growth in BG-11 medium. Both species exhibited higher biomass and chlorophyll content in BBM and BG-11 media compared to CHU-10. For both Chlorella vulgaris and Chlamydomonas reinhardtii, BBM was the most favorable medium for accumulating fatty acids with significantly higher total concentrations compared to BG-11 and CHU-10. Regarding fatty acid composition percentages, BBM had the highest fatty acid content for Chlorella vulgaris while CHU-10 had the highest fatty acid content for Chlamydomonas reinhardtii. These findings highlight the potential of Chlorella vulgaris and Chlamydomonas reinhardtii for biodiesel production with BBM and BG-11 media showing promise for optimizing growth and lipid yield.